Pengaruh Perkembangan Bank Umum Syariah Terhadap Pertumbuhan Ekonomi Indonesia Periode 2010-2015 - Firmansyah Putra; Muhammad Nafik Hadi Ryandono (Universitas Airlangga, 2017)
The study aims to examines the influence of Islamic banks on economic growth in Indonesia during the period 2010–2015. Secondary data that were used in this research were in the form of monthly time series and cross-section data during the year 2010–2015. The data were obtained based on monthly statistical banking report from Bank Indonesia (BI) andmonthly statistical reports of the Monthly Industrial Production Index in the Large and Medium scale from Central Bureau of Statistics (BPS) of Indonesia and also annual report from each islamic banks that conclude in this observation. Total assets, and total financing as variables that are representing the Islamic bank. GDP (Gross Domestic Product) is the variable that representing economic growth. By using Multiple Regression Analysis, the result shows that generally, Islamic banking affects economic growth in Indonesia.